Primary cilia and organogenesis: is Hedgehog the only sculptor? - Tasouri, Evangelia; Tucker, Kerry (Cell & tissue research, 2011)
The primary cilium is a small microtubule-based organelle projecting from the plasma membrane of practically all cells in the mammalian body. In the past 8 years, a flurry of papers has indicated a crucial role of this long-neglected organelle in the development of a wide variety of organs, including derivatives of all three germ layers. A common theme of these studies is the critical dependency of signal transduction of the Hedgehog pathway upon functionally intact cilia to regulate organogenesis. Another common theme is the role that the cilium plays, not necessarily in the determination of the embryonic anlagen of these organs, although this too occurs but rather in the proliferation and morphogenesis of the previously determined organ. We outline the various organ systems that are dependent upon primary cilia for their proper development and we discuss the cilia-dependent roles that Sonic and Indian Hedgehog play in these processes. In addition and most importantly for the field, we discuss the controversial involvement of another major developmental pathway, Wnt signaling, in cilia-dependent organogenesis.